Distribuição espacial e dinâmica temporal da alga epizoária Basicladia chelonum associada ao cágado Phrynops geoffroanus no rio Uberabinha, Minas Gerais - Zanelli, Helise Regina Rosa (2006)
Studies were developed about a population of Basicladia chelonum epizoic algae over the Phrynops geoffroanus turtle carapace captures in an urban area of Uberabinha River, city of Uberlândia, MG (18°54 34,5"S e 48°18 20,4"W). The fieldwork was accomplished during the morning, in the middle and end of each season, from August 2004 to June 2005, totalizing eight samples. The area was distinguished about flora composition in the river s margins, temperature and relative air humidity, luminosity intensity and some physical and chemical water parameters. Three hundred and twenty Phrynops geoffroanus individuals were captured (205 female, 115 males), each collect with 40 individuals. After the capture, the turtles were transported to the Reptile Sector of Uberlândia s Federal University, they were marked individually, their sexes identified and sheltered in concrete tanks. After this procedure, morphometrical and corporeal mass data were taken, and the front and back limbs, head, neck, tail, ventral part of the carapace marginal shields and plastral of the turtle were observed about the presence of algae. In the carapace, when present, the algae were plotted in acetate sheets and the area of covering was estimated through Autodesk s AutoCaAD 2002 software help. Samples of algae were collected through superficial scratching of the carapace and fixed in formaldehyde at 4%. For the study of dynamics of Basicladia chelonum were analyzed characteristics considered relevant as: 1) presence of sporangium (>75% abundant, 25-50% frequent, <10%); 2) plant height (biggest fiber); and 3) length and diameter of cells (basal, medial and sporangium). After sampling of epizoic algae, the Phrynops geoffroanus individuals were reintroduced in the same capture point. Were encountered correlations between air temperature and water temperature, dissolved oxygen an pH and oxygen chemical demand, rain with concentration of iron, ammonium, total nitrogen, total phosphorus, electrical conductivity and pH, totals dissolves solids, obscureness and concentrations of nitrate, nitrite, iron and ammonium. The study area, the Uberabinha River is under great human influences, probably due to the unloading of domiciliary and industrials waste, mainly deriving of the Tabocas stream. In all the samples occurrences of epizoic algae were observed in different body parts of Phrynops geoofroanus individuals. The porcentage of algae coverage was higher in September and lower in the months of March and June (F=2,28; p<0,05). The algae coverage also was different between sex. The males showed more percentage of coverage than females (F=8,60; p<0,05). Occurred a high number of individuals with algae in the rear marginal scute and lower in the front scute and in the bridge marginal scute (F=35,27; p<0,05) were observed sporangium in the all the samples of analyzed algae. They were abundant in the algae collected in September (F=5,86; p<0,05) and in the front marginal shields (F=114,62; p<0,05), and rare in collections of August, October, March and June (F=4,85; p<0,05) and in the costal scute, rear marginal scute and in the vertebral scute (F=54,13; p<0,05). The morphometrical characters of the algae evidenced the seasonality does not interfered in the populational dynamics of Basciladia chelonum, although it had variated significantly during the study period. Probably, abrasion, turbulence, dissection and concentration of nutrients in the river s water could be interfering in the amount of algae coverage, also in the growing and developing of these in the different carapace parts of turtle.